2020
DOI: 10.1002/jimd.12247
|View full text |Cite
|
Sign up to set email alerts
|

AADC deficiency from infancy to adulthood: Symptoms and developmental outcome in an international cohort of 63 patients

Abstract: Aromatic l‐amino acid decarboxylase deficiency (AADCD) is a rare, autosomal recessive neurodevelopmental disorder characterized by impaired synthesis of dopamine, noradrenaline, adrenaline and serotonin, leading to a complex syndrome of motor, behavioral, and autonomic symptoms. This retrospective study assessed the symptoms and developmental outcome of a large international cohort of patients with AADCD via physician and/or caregiver responses to a detailed, standardized questionnaire. Sixty‐three patients (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
2
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 18 publications
7
79
2
21
Order By: Relevance
“…This magnitude of motor function improvement in our subjects would not be expected to occur in the natural course of AADC de ciency for patients in this age range (4-9 years) who have severe motor impairment. In a retrospective study of 63 patients (age range 6 months to 36 years), 11 subjects with a mild-moderate disease phenotype were able to walk independently 4 . In those 11 subjects, the potential for motor development was evident in early childhood, with all having attained the ability to sit independently by age 4 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This magnitude of motor function improvement in our subjects would not be expected to occur in the natural course of AADC de ciency for patients in this age range (4-9 years) who have severe motor impairment. In a retrospective study of 63 patients (age range 6 months to 36 years), 11 subjects with a mild-moderate disease phenotype were able to walk independently 4 . In those 11 subjects, the potential for motor development was evident in early childhood, with all having attained the ability to sit independently by age 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Oculogyric crises (OGC) are one of the cardinal features of the disease, and are characterized by episodes of intermittent or sustained tonic vertical (usually upward), horizontal, or convergent deviation of the eyes, sometimes accompanied by dystonia or other involuntary movements of the face and body. Episodes typically last for hours and occur several times per week 4 . Catecholamine and serotonin de ciency also cause non-motor symptoms such as emotional lability, sleep disturbance, and excessive sweating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012 12 02), and the patient registry of the International Working Group on Neurotransmitter Related Disorders (iNTD: https://www.intd-registry.org/ ). These projects have described in detail the natural history of more than 40 different IMDs and their disease variants, evaluated the impact of interventional and non-interventional parameters (including evaluation of newborn screening programmes for IMDs if available), and developed evidence-based care protocols being the basis for national guidelines and being translated into information brochures for patients, families and healthcare professionals [ 2 4 , 7 13 , 13 , 14 , 14 18 , 23 ]. Thereby, the E-IMD, E-HOD and iNTD family of rare disease registries has confirmed that networking activities and the establishment of patient registries have a relevant impact for improving the health of patients with IMDs, and for harmonizing diagnostic algorithms, therapy and long-term follow-up and care on a European and international level.…”
Section: Introductionmentioning
confidence: 99%
“…The malfunction of AADC causes a rare inborn neurometabolic disorder, named AADC deficiency (MIM#608643), which was first described by Hyland and Clinton in 1990 [ 1 ]. The most commonly reported symptoms of AADC deficiency include neurodevelopmental delay, hypotonia, oculogyric crises, and a complex movement disorder with autonomic features [ 2 , 3 , 4 ]. The cerebrospinal fluid neurotransmitters profile, based on clinical symptoms, is highly indicative for the diagnosis of AADC deficiency [ 3 ].…”
Section: Introductionmentioning
confidence: 99%